2014
DOI: 10.1016/j.foodqual.2014.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variation in oronasal perception and the relative effects of PROP and Thermal Taster Status

Abstract: Joanne (2014) Phenotypic variation in oronasal perception and the relative effects of PROP and Thermal Taster Status. Food Quality and Preference, 38. pp. 83-91. Abstract Individual variation in taste perception has long been investigated, particular in relation to PROP taster status (PTS). Recently, a new marker has been identified, Thermal Taster Status (TTS), whereby individuals are categorised as thermal tasters (TTs) or thermal non-tasters (TnTs) based on their ability to perceive taste solely from temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 41 publications
9
57
0
Order By: Relevance
“…Figure 1 shows the taste qualities (%) experienced by thermal tasters after application of the TED; the proportions are similar to those reported by Pickering and Klodnicki [18]. The proportion of participants classified as TTs in this study was 44 %, which is within the range found in other reports (27 % [9], 31 % [Thibodeau M, Bajec MR, Pickering GJ: Orosensory responsiveness, thermal tasting and alcohol behavior, Submitted], 50 % [11]). …”
Section: Thermal-taster Status Determinationsupporting
confidence: 86%
See 4 more Smart Citations
“…Figure 1 shows the taste qualities (%) experienced by thermal tasters after application of the TED; the proportions are similar to those reported by Pickering and Klodnicki [18]. The proportion of participants classified as TTs in this study was 44 %, which is within the range found in other reports (27 % [9], 31 % [Thibodeau M, Bajec MR, Pickering GJ: Orosensory responsiveness, thermal tasting and alcohol behavior, Submitted], 50 % [11]). …”
Section: Thermal-taster Status Determinationsupporting
confidence: 86%
“…While there was an overall effect of TTS, a significantly more limited range of food items varied with the phenotype than we expected, given the heightened intensity experienced by TTs for a wide range of orosensations reported in simple aqueous solutions [8,9,11,12], wine [14] and beer [15]. While it is possible the analyses were underpowered due to the sample size, it is noteworthy that this enhanced acuity has only been demonstrated robustly to date in solutions and not with solid or semisolid matrices, perhaps indicating that wider palate stimulation is necessary to recruit sufficient receptors to confer the greater responsiveness of TTs.…”
Section: Orosensationmentioning
confidence: 71%
See 3 more Smart Citations